DISTRIBUTION OF SNOW COVER BY CLIMATIC ZONES OF THE TRANSBOUNDARY PYANJ RIVER BASIN - Normatov Inom Sherovich; Goncharuk Vladislav Vladimirovich; Normatov Parviz Inomovich; Odinaev Qodir Nodirovich (Scientific Journal of Pedagogy and Economics, 2020)
The results of monitoring the processes of the snow cover accumulation on upstream of the Transboundary Pyanj river of the Central Asia are presented. It is found that the snow cover formation and the spatial distribution of atmospheric precipitation in the Pamir mountain is mainly determined by the orography of the terrain.